2008
DOI: 10.1007/s10295-008-0426-6
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the recombinant invertase INVB from Zymomonas mobilis on Nylon-6

Abstract: The recombinant invertase INVB (re-INVB) from Zymomonas mobilis was immobilized on microbeads of Nylon-6, by means of covalent bonding. The enzyme was strongly and successfully bound to the support. The activity of the free and immobilized enzyme was determined, using 10% (w/v) sucrose, at a temperature ranging between 15 and 60 degrees C and a pH ranging between 3.5 and 7. The optimal pH and temperature for the immobilized enzyme were 5.5 and 25 degrees C, respectively. Immobilization of re-INVB on Nylon-6 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Other studies have been developed with immobilized algal cells to remove nutrients (N and P) from wastewater, phenol and hexavalent chromium [14][15][16][17]. Similarly, the immobilization of Zymomonas and Saccharomyces have been used for the bio-ethanol production from waste materials [7][8][9][10][18][19][20].…”
Section: Tecnología De Inmovilizaciónmentioning
confidence: 99%
“…Other studies have been developed with immobilized algal cells to remove nutrients (N and P) from wastewater, phenol and hexavalent chromium [14][15][16][17]. Similarly, the immobilization of Zymomonas and Saccharomyces have been used for the bio-ethanol production from waste materials [7][8][9][10][18][19][20].…”
Section: Tecnología De Inmovilizaciónmentioning
confidence: 99%
“…Previously, enzymes have been frequently stabilized by crosslinking to solid supports and entrapment within matrices (Betancor and Luckarift, 2008;Bryjak et al, 2008;Dizge et al, 2008;Mateo, et al, 2007;Polizzi et al, 2007;Vallejo-Becerra et al, 2008). The relevant immobilization methods have been reviewed by Sheldon (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GA may react readily with the protein in the lipid bilayer of cell membrane [27,28]. Its aldehyde groups can also cross-link the amino groups on PEI-coated materials and the surfaces to promote cell-support interaction by chemical bonding [28,29].…”
Section: Surface Treatment Of Fibersmentioning
confidence: 99%
“…Thus, it can be concluded that PEI-GA modification can be an affective method to improve cell immobilization on fibrous matrices [28,29]. PEI is non-toxic and has been approved by the FDA for use in potable water [22].…”
Section: Static Adsorption Of Cells To Different Fibersmentioning
confidence: 99%
See 1 more Smart Citation